Clinical efficacy analysis of chemotherapy of isolated neck lymphatic metastasis in advanced epithelial ovarian cancer - Hong Liu; Min Luo; Chunrong Peng; Xinghan Cheng; Dengfeng Wang; Jianming Huang; Guonan Zhang (BMC Cancer)
Abstract Objective The aim of this study was to retrospectively investigate the efficacy of chemotherapy for neck lymph node metastasis (NLNM) by determining the characteristics and survival of patients with isolated NLNMs metastases from epithelial ovarian carcinoma (EOC) at stage IV of the Federation of Gynecology and Obstetrics (FIGO). Methods The clinicopathological characteristics and survival outcome of 24 cases with stage IV FIGO EOC with isolated NLNM were retrospectively analyzed between December 1, 2014, and November 30, 2021. Results Among the 24 patients, 2 (8.3%) underwent primary debulking surgery (PDS), 21 (87.5%) received neoadjuvant chemotherapy(NACT) followed by interval debulking surgery (IDS), and 1 (4.2%) received chemotherapy alone. Additionally, 13 (54.2%) cases achieved abdominal R0 debulking, while 11(45.8%) cases achieved R1/R2 debulking. The chemotherapy response of NLNMs included complete response (8/24, 33.3%), partial response (15/24,62.5%), or stable disease (1/24,41.7%). None of the patients received resection or radiotherapy of NLNMs. Recurrence was observed in 15 (62.5%) patients, with only 2 experiencing recurrence of NLNMs. The median progression-free survival (PFS) and overall survival (OS) were 35 months and 48 months, respectively. R0 debulking led to a significantly longer PFS (not reached) and OS (57 months) compared to non-R0 debulking (PFS: 10 months, P = 0.001; OS: 22 months, P = 0.001). Interestingly, patients with EOC with lymphatic recurrence had better OS ( 57 months) than did those with abdominal or distant recurrence (OS: 29 months; P = 0.012). Conclusions Chemotherapy is an effective treatment for neck lymph nodes metastasis, and a favorable response to chemotherapy could eliminate the necessity for NLNM resection or radiotherapy. Effective control of abdominal disease with surgery may be a critical factor in managing FIGO stage IV EOC patients with isolated NLMNs.